Humanitarian logistics : performance measurement and the role of shipping - Tan, Hui Yun. (2013)
The increase in natural disasters and aid expenditures has resulted in more emphasis on humanitarian logistics, with interest in the area of performance management and accountability growing. However, humanitarian logisticians have traditionally not seen the need to measure their performance, thus resulting in them falling behind the commercial sector in performance measurement.